2009
DOI: 10.1038/nm.1995
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of interleukin-21 in the epidermal hyperplasia of psoriasis

Abstract: T cells are crucial mediators of the skin damage in psoriasis. We here show that interleukin-21 (IL-21), a T cell-derived cytokine, is highly expressed in the skin of individuals with psoriasis, stimulates human keratinocytes to proliferate and causes epidermal hyperplasia when injected intradermally into mice. In the human psoriasis xenograft mouse model, blockade of IL-21 activity resolves inflammation and reduces keratinocyte proliferation. Blocking IL-21 may represent a new therapeutic strategy in psoriasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
162
5
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 181 publications
(178 citation statements)
references
References 8 publications
7
162
5
4
Order By: Relevance
“…Th17 cells and their downstream effector molecules, which include IL-17A, IL-17F, IL-22, IL-21 and TNF-a, are found at increased levels in psoriatic skin and circulation. [49][50][51][52] Moreover, psoriatic skin lesions also contain high mRNA and protein levels of IL-23 compared with non-lesional and normal skin and IL-23 has been found to be produced mainly by the activated macrophages and DCs. [53][54][55] Intradermal injection of IL-23 or IL-21 in mice can stimulate keratinocytes proliferation and cause epidermal hyperplasia (acanthosis), which is one of the most significant features in human psoriasis.…”
Section: Is Psoriasis a Th1 And/or Th17 Cell-mediated Inflammatory Skmentioning
confidence: 99%
See 1 more Smart Citation
“…Th17 cells and their downstream effector molecules, which include IL-17A, IL-17F, IL-22, IL-21 and TNF-a, are found at increased levels in psoriatic skin and circulation. [49][50][51][52] Moreover, psoriatic skin lesions also contain high mRNA and protein levels of IL-23 compared with non-lesional and normal skin and IL-23 has been found to be produced mainly by the activated macrophages and DCs. [53][54][55] Intradermal injection of IL-23 or IL-21 in mice can stimulate keratinocytes proliferation and cause epidermal hyperplasia (acanthosis), which is one of the most significant features in human psoriasis.…”
Section: Is Psoriasis a Th1 And/or Th17 Cell-mediated Inflammatory Skmentioning
confidence: 99%
“…[53][54][55] Intradermal injection of IL-23 or IL-21 in mice can stimulate keratinocytes proliferation and cause epidermal hyperplasia (acanthosis), which is one of the most significant features in human psoriasis. 51,56 Further studies demonstrated that IL-22, IL-17A as well as CC chemokine receptor (CCR) 6 are all required for IL-23-induced psoriasis-like skin inflammation. [57][58][59] In addition, IL-22 was also shown to be critical in another murine psoriasiform model triggered by topical application of Toll-like receptor 7/8 agonist Imiquimod.…”
Section: Is Psoriasis a Th1 And/or Th17 Cell-mediated Inflammatory Skmentioning
confidence: 99%
“…The contribution of IL-21 to a number of autoimmune diseases, including systemic lupus erythematosus, Sjögren's syndrome, rheumatoid arthritis, experimental allergic autoimmune encephalomyelitis, psoriasis, diabetes mellitus, and inflammatory bowel disease, was reported (13)(14)(15)(16)(17)(18)(19). Elevated IL-21 levels were found in lupus-prone BXSB.Yaa mice, and autoimmune features were attenuated in BXSB.Yaa and MRL-Fas lpr mice following genetic deletion of IL-21R or IL-21 blockade (20)(21)(22)(23).…”
Section: Nterleukin-21 Is a Member Of The Type I Cytokine Family Wimentioning
confidence: 99%
“…In the skin, Th17 cells secrete cytokines including IL17, IL21, and IL22; the latter found to lead to proliferation of keratinocytes [14]. Likewise, intradermal injection of IL21 has been shown to stimulate human keratinocytes to proliferate and causes epidermal hyperplasia in murine models [15]. This pathologic hyperproliferation of keratinocytes leads to the characteristic thickening of the epidermis observed in psoriasis [14,16].…”
Section: Il23 and Psoriatic Arthritismentioning
confidence: 99%